Lime-based adsorbent for flue gas treatment equipment and process for making the same

By using lime-based adsorbents with high content of Ca(OH)2 and highly absorbent polymers or cellulose ethers in the circulating dry scrubber, the problem of water addition restrictions in the circulating dry scrubber is solved, and the smoke is realized Stable fluidity and efficient operation with medium and high water content.

CN114599449BActive Publication Date: 2025-01-03LHOIST RECH & DEV SA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080074535.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-23
Filing Date
2020-09-22
Publication Date
2025-01-03
Estimated Expiration
2040-09-22

AI Technical Summary

Technical Problem

There are limitations in the addition of water in the circulating dry scrubber technology, which leads to adhesion and blockage on the recirculation circuit and reactor pipeline wall during the flue gas treatment, affecting the operational stability.

Method used

Using a lime-based adsorbent, which comprises at least 70% Ca(OH)2 and 0.2% to 10% of highly absorbent polymer or cellulose ether as additives, the quicklime is cured through a non-wet pathway to form high Adsorbents with adsorption capacity and good fluidity can maintain multiple cycles during flue gas treatment and release water vapor.

Benefits of technology

The capacity of water content in flue gas treatment is significantly improved, the adhesion performance and blockage phenomenon is reduced, the good fluidity of the adsorbent is maintained, and the efficiency and stability of flue gas treatment are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114599449B_ABST
    Figure CN114599449B_ABST
Patent Text Reader

Abstract

A lime-based sorbent suitable for flue gas treatment processes, comprising at least 70% by weight of Ca(OH)2 and at least 0.2% to at most 10% by weight of a first additive selected from the group of hydrogels of natural or synthetic origin, in particular superabsorbent polymers (SAP) or from the group of cellulose ethers or a combination thereof, a premix used in the process for manufacturing the sorbent, a process for manufacturing the sorbent and the use of the sorbent in a flue gas treatment process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] In a first aspect, the present invention relates to an adsorbent suitable for flue gas treatment equipment. In a second aspect, the present invention relates to a premix for a manufacturing process of the adsorbent. In a third aspect, the present invention relates to a process for manufacturing an adsorbent suitable for flue gas treatment equipment. In a fourth aspect, the present invention relates to the use of the adsorbent in a flue gas treatment process. In a fifth aspect, the present invention relates to a process for using the adsorbent for flue gas treatment. Background Art

[0002] Combustion flue gases include substances that are considered harmful to the environment, and flue gas treatment is increasingly being performed in order to remove or neutralize those harmful substances and pollutants. A variety of processes are used for flue gas treatment, including scrubbing techniques. The first type of such technology is wet scrubber technology using a wet scrubber unit, which typically works by contacting the target compound or particulate matter with a scrubbing liquid, which can be water for dust or a solution or suspension of a reagent that targets a specific compound. The second type of scrubbing technology includes dry scrubbing systems and semi-dry scrubbing systems, which are also called semi-wet scrubbing systems. Compared to wet scrubber units, those systems do not saturate the treated flue gas with moisture. In some cases, no moisture is added, while in other cases, only an amount of moisture that can evaporate in the flue gas without condensing is added. The main use of dry or semi-dry scrubbing devices involves capturing and removing acid gases such as sulfur oxides and hydrochloric acid, which mainly come from combustion sources. In the present disclosure, the term "cycling dry" in the expression "cycling dry scrubber device" or "cycling dry scrubber equipment" or "cycling dry scrubber system" or "cycling dry scrubber unit or cycling dry scrubber facility" refers to a "cycling dry scrubber" or a "cycling semi-dry scrubber".

[0003] The cyclic dry scrubber (CDS) technology was first developed for SO2 removal in coal-fired power plants. Today, it is also used for flue gas treatment of industrial furnaces and boilers that use biomass, industrial or municipal waste as fuel. CDS technology generally implements a CDS process and involves a CDS unit. A CDS unit can be integrated in a more global CDS facility. The CDS process is based on the recycling of residues collected from a particle control device, which residues include unreacted adsorbent, reaction products and optionally fly ash.

[0004] A CDS unit typically includes a reactor for receiving flue gases and an adsorbent, which is typically a calcium-based adsorbent. The reactor is followed by a particle control device that filters solids (also called residues and including unreacted adsorbent, reaction products, and optionally fly ash) from the released gases. These solids are then partially recycled to the reactor through a recirculation loop. Some fresh adsorbent may be added to the reactor periodically or continuously before or after. In most cases, water is injected into the reactor and / or onto the solids for temperature control to improve pollutant removal performance and reactivate the residue. Some CDS facilities have CDS units and may include a hydrator (also called a slaking unit). They use quicklime CaO that is hydrated before entering the CDS unit in the CDS process. Some other CDS facilities do not include any hydrators, and the fresh adsorbent injected is slaked lime.

[0005] In a first way of operating the CDS process, the residue is moistened before reinjection into the reactor. In a second way of operating the CDS process, water is injected directly into the reactor.

[0006] Unfortunately, even though CDS technology is effective in removing pollutants, there are limitations on the amount of water that can be added, and the addition of water remains a key factor in the removal of these pollutants. Indeed, it is known that higher capture levels of acid gases can be achieved by increasing the flue gas humidity, while keeping in mind that falling below the dew point may cause corrosion problems, especially in the reactor.

[0007] The maximum water content observed on a commercial scale, relative to the mass of dry recycled residue, is 10% by weight, more often between 2% and 7% by weight, in the case where the residue is moistened before reinjection into the reactor. Above a water content of 10%, adhesion and plugging phenomena occur on the walls of the pipes both in the recycling loop and in the reactor, making the operation unstable until the flue gas cleaning unit is completely stopped.

[0008] In the case where water is injected directly into the reactor, even if the water is not carried along by the recirculating material, clogging phenomena are still observed to occur in the reactor, thereby negatively affecting the flue gas treatment process.

[0009] There is a need to provide sorbents and flue gas treatment processes that allow CDS process operation in which the water content can be increased without negatively affecting the recycle dry scrubbing process. It is particularly desirable to at least reduce the adhesion and plugging of recycle material on the walls of the pipes in the recycle loop and in the reactor.

[0010] Document WO2018185328 of the applicant discloses an adsorbent for a circulating dry scrubber, comprising at least 50% by weight of Ca(OH)2 and between 0.5% and 8% of silicon or aluminum or a combination thereof, expressed in their elemental form, relative to the total weight of the adsorbent in dry form, wherein the adsorbent further comprises between 1% and 12% by weight of bound water relative to the total weight of the adsorbent in dry form, and wherein between 1% and 40% of the molar ratio of calcium is neither in the form of Ca(OH)2 nor in the form of CaCO3 nor in the form of CaO. This adsorbent is obtained by a process comprising the following steps:

[0011] - providing quicklime and water in a hydrator;

[0012] - slaking the quicklime in the hydrator by a non-wet route;

[0013] - Collection of lime-based adsorbent at the outlet of the hydrator;

[0014] Characteristically, the process comprises a further step of adding at least a first additive, the first additive comprising:

[0015] - a compound comprising silicon, preferably selected from the group of silicates, sodium silicates, metasilicates, sodium metasilicates, diatomaceous earth, diatomaceous earth, diatomaceous earth, precipitated silica, rice husk ash, silica fume, perlite, silicic acid, amorphous silica, calcium silicate or combinations thereof, and / or;

[0016] - a compound comprising aluminum, preferably selected from the group of aluminates, sodium aluminates, aluminum hydroxide, boehmite, calcium aluminate or combinations thereof, and / or;

[0017] - a compound comprising silicon and aluminum, preferably selected from the group of aluminosilicates, sodium aluminosilicates, fly ash, blast furnace slag, vermiculite paper ash or a combination thereof;

[0018] Before or during the slaking step, the molar ratio between silicon or aluminium or a combination thereof and calcium supplied to the hydrator is equal to or lower than 0.2 and equal to or higher than 0.02.

[0019] Although such adsorbents exhibit good performance in terms of capturing pollutants and flowability in CDS facilities, there is a need for alternative absorbent compositions with improved performance obtainable from different raw materials. Summary of the invention

[0020] According to a first aspect, the present invention relates to a lime-based sorbent suitable for a flue gas treatment process, the lime-based sorbent comprising:

[0021] - at least 70% Ca(OH)2, preferably at least 80% Ca(OH)2, more preferably at least 90% Ca(OH)2, more preferably at least 95% Ca(OH)2 in a weight proportion relative to the total weight of the lime-based sorbent in dry form after drying at 150°C until constant weight, and;

[0022] - a first additive chosen from the group of hydrogel-forming materials of natural or synthetic origin, in particular superabsorbent polymers (SAP), or from the group of cellulose ethers, or a combination thereof, in a weight ratio of at least 0.2% to at most 10%, preferably at least 1% to at most 5%, more preferably at least 1.2% to at most 2.5%, relative to the total weight of the lime-based adsorbent in dry form after drying at 150° C. until constant weight.

[0023] The Ca(OH)2 present in the adsorbent can be measured qualitatively and quantitatively by conventional techniques known to those skilled in the art. The amount of calcium is measured by XRF, the crystal structure of the compound is analyzed by XRD, and the ratio of calcium carbonate and / or calcium oxide (if present) and calcium hydroxide is determined by thermogravimetric analysis on a sample dried at 150°C until constant weight.

[0024] The presence of additives in the adsorbent can be measured qualitatively and quantitatively by NMR. After preparation of a sample which can be dried at 150° C. until constant weight and mixed in a deuterated solvent or a mixture of deuterated solvents (preferably a mixture of D2O and CD3CN), the adsorbent can be measured qualitatively and quantitatively by NMR. 1 HNMR or 13 CNMR or a combination thereof, the additive in the adsorbent is detected using a probe HR-MAS (High Resolution Magic Angle Spinning) for analysis in a semi-liquid state, or by solid analysis on a solid sample which can be dried at 150°C until constant weight. 1 HNMR measures the additive in the adsorbent. Quantitative measurement by NMR can be performed by comparison with a calibration curve obtained by preparing adsorbent samples including various concentrations of the additive.

[0025] The term "hydrogel-forming material" according to the present invention encompasses a dehydrated hydrogel (i.e., in powder form) or a hydrogel with entrapped water. Also included within the scope of this phrase are any intermediate forms, such as, for example, a hydrogel-forming material that is in powder form while having entrapped ambient humidity, e.g., comprising 5% water or 10% water, but still being a powder.

[0026] Preferably, the first additive is selected from:

[0027] - the group of hydrogel-forming materials of synthetic origin, which includes polyacrylates, polyacrylic acid, cross-linked polyacrylates and polyacrylic acid or cross-linked acrylamide and acrylate copolymers, in particular those partially neutralized with sodium and / or potassium, or

[0028] - a group of hydrogel-forming materials of natural origin comprising guar gum, alginate, dextran or xanthan gum or a combination thereof, and / or;

[0029] - The group of cellulose ethers which comprises hydroxyalkyl or carboxyalkyl cellulose ethers, in particular carboxymethyl cellulose or hydroxyethyl methyl cellulose (HEMC).

[0030] Preferably, the super absorbent polymer is selected from one or more super absorbent polymers of synthetic origin, selected from crosslinked polymers of acrylic acid or methacrylic acid, crosslinked graft copolymers of polysaccharide / acrylic acid or methacrylic acid, crosslinked terpolymers of acrylic acid or methacrylic acid / acrylamide / sulfonated acrylamide and their alkaline earth metal salts or alkali metal salts.

[0031] Preferably, the monomers selected for preparing the superabsorbent polymer are selected from acrylamide, acrylic acid, ATBS (acrylamido tert-butyl sulfonate), NVP (N-vinyl pyrrolidone), acryloylmorpholine and / or itaconic acid, each of which is partially or completely salified.

[0032] Preferably, the superabsorbent polymer is a homopolymer or crosslinked copolymer of partially or completely salified acrylic acid. The superabsorbent polymer can be made from hydrophilic monomers, such as cationic polymers, including diallyldialkylammonium, diallylaminoalkyl (meth)acrylate, (meth)acrylamidedialkylaminoalkyl, their quaternary ammonium quaternary salts or their acids, more particularly dimethylaminoethyl acrylate (ADAME), dimethylaminoethyl methacrylate (MADAME), acrylamidopropyltrimethylammonium chloride (APTAC) and / or methacrylamidopropyltrimethylammonium chloride (MAPTAC).

[0033] The synthetic superabsorbent polymer is typically crosslinked with a crosslinking agent selected from N,N-methylenebisacrylamide (MBA), ethylene glycol dimethacrylate, 1,1,1-trimethylolpropane triacrylate, tetraallyloxyethane, tetraallylammonium chloride, divinylbenzene, metal salts or any crosslinking agent known in the art.

[0034] Superabsorbent polymers are well known commercially available polymers.

[0035] According to the present invention, the hydrogel-forming material has a water adsorption capacity of less than 400 g / g, preferably equal to or less than 350 g / g, more preferably equal to or less than 300 g / g, in particular equal to or less than 250 g / g, and more in particular equal to or less than 200 g / g, the water adsorption capacity being expressed as the weight of deionized water relative to the weight of the polymer.

[0036] More particularly, according to the invention, the hydrogel-forming material has a water adsorption capacity, expressed as the weight of deionized water relative to the weight of the polymer, equal to or greater than 80 g / g, preferably equal to or greater than 100 g / g.

[0037] Advantageously, the hydrogel-forming material has a water adsorption capacity expressed as the weight of deionized water relative to the weight of the polymer of between 100 and 200 g / g, more preferably between 120 and 180 g / g such as, for example, about 150 g / g.

[0038] The first additive selected from the hydrogel forming material according to the present invention is capable of capturing water for its conditioning at relatively low temperatures, such as about ambient temperature, but also allows the release of water in the CDS unit or dry scrubber injection (DSI) unit in the form of steam, also in the presence of Ca(OH)2, at operating temperatures between 50°C and 350°C and preferably between about 150°C and 180°C. Furthermore, the lime-based sorbent combining the hydrogel forming material and Ca(OH)2 is preferably kept in powder form for injection during flue gas treatment.

[0039] The lime-based sorbent according to the present invention is sustained in multiple pass cycles through a CDS facility in flue gas treatment, during which it alternates between a water capture step (eg, in a conditioning drum) and a water release step (in a CDS unit).

[0040] In an embodiment, the lime-based sorbent according to the present invention further comprises sodium, the amount of sodium in the lime-based sorbent, expressed in the form of its equivalent Na2O oxide, measured by XRF, relative to the total weight of the sorbent in dry form, being at least 0.1%, preferably at least 0.3%, preferably at least 0.5%, preferably at least 0.7%, preferably at most 15%, preferably at most 7%, preferably at most 5%, preferably at most 2.5% by weight.

[0041] Preferably, the lime-based adsorbent according to the present invention has a 2 / g, preferably at least 10m 2 / g, more preferably at least 20m 2 / g, preferably at least 40m 2 / g, the BET specific surface area is measured by nitrogen adsorption manometry after degassing at 190°C in vacuum for at least 2 hours and calculated according to the multi-point BET method as described in ISO 9277 / 2010E standard. In an embodiment of the present invention, the adsorbent has a surface area of ​​1.3 m / s. 2 / g and 20m 2 / g BET specific surface area between.

[0042] Advantageously, the lime-based adsorbent according to the invention has a 3 / g, preferably at least 0.05cm 3 / g, more preferably at least 0.1cm 3 / g, more preferably at least 0.15cm 3 / g, more preferably at least 0.2cm 3 / g of total BJH pore volume, the total BJH pore volume being determined by nitrogen adsorption manometry after degassing at 190°C in vacuum for at least 2 hours and calculated according to the multi-point BJH method as described in ISO 9277 / 2010E standard. In an embodiment of the present invention, the adsorbent has a pore volume between 0.01 and 0.15 cm 3 / g of BJH pore volume.

[0043] The particle size of lime-based adsorbents, slaked lime and additives can be measured by two methods, depending on the characteristics of the sample. The first method is sieve analysis, in which the dry sample is passed through a series of sieves with decreasing mesh sizes and the fraction retained on each mesh is weighed. max The value is defined as the retained portion of the powder below 2% of the sieve size by weight of the powder, and the second d min The value is defined as the sieve size at which the retained portion of the powder is above 90% by weight of the powder. Due to the limitation of the mesh size of the sieve, this method is used for particles with a d value of more than 30 μm. min For sieves with a mesh size of less than 100 μm, depressions can be applied to force the particles to pass through the sieves.

[0044] A second method for measuring the particle size distribution of lime-based adsorbents, slaked lime and additives is laser particle size measurement after sonication in a solvent such as methanol, where the sample is not soluble or gelled. max The value is defined and corresponds to d 98 , and the second d min The value is defined and corresponds to d 10 The notation dx refers to the particle size distribution of a sample of particles, wherein x% of the particles have a size below a certain value expressed in μm.

[0045] Preferably, the lime-based adsorbent according to the invention has a d value less than or equal to 1 mm, preferably less than or equal to 400 μm, more preferably less than or equal to 200 μm, more preferably less than or equal to 100 μm, preferably less than or equal to 80 μm, preferably less than or equal to 40 μm, more preferably less than or equal to 30 μm. max .d min It is preferably greater than or equal to 1 μm, preferably greater than or equal to 2 μm, more preferably greater than or equal to 5 μm, more preferably greater than or equal to 10 μm, more preferably greater than or equal to 20 μm, more preferably greater than or equal to 30 μm.

[0046] In a preferred embodiment of the lime-based sorbent according to the present invention, the Ca(OH)2 and the first additive are in the form of a powder blend comprising:

[0047] - Powdered particles of slaked lime, the powdered particles having a max Value and d min a particle size distribution within a first range of values, and;

[0048] - powdery particles of the first additive, the powdery particles having a max Value and d min The particle size distribution is within a second range of values, and the second range overlaps with or is equal to the first range.

[0049] In order to prevent the slaked lime particles from being separated from the additive particles, it is very important that the particle size distribution of the powdered particles of slaked lime and the particle size distribution of the powdered particles of the additive are close to each other.

[0050] According to a second aspect, the present invention relates to a premix for use in a process for manufacturing a lime-based sorbent, the premix comprising:

[0051] - quicklime in a proportion by weight of at least 70%, more preferably at least 90%, relative to the total weight of said premix in dry form after drying at 150° C. until constant weight, and;

[0052] - a first additive chosen from the group of hydrogel-forming materials of natural or synthetic origin, in particular superabsorbent polymers (SAP), or from the group of cellulose ethers, or a combination thereof, in a weight proportion of at least 0.2% to at most 10%, preferably at least 1% to at most 5%, more preferably at least 1.2% to at most 2.5%, relative to the total weight of said premix in dry form after drying at 150° C. until constant weight.

[0053] For flue gas treatment plants having a hydrator in the premix treatment, providing such a premix may be more advantageous in terms of logistics and costs.

[0054] Preferably, in the premix according to the present invention, the powdered quicklime and the powdered first additive are in the form of a powder blend comprising:

[0055] - Powdered particles of quicklime, the powdered particles having a max Value and d min a particle size distribution within a third range of values, and;

[0056] - powdery particles of the first additive, the powdery particles having a max Value and d min The particle size distribution is within a fourth range of values, and the fourth range overlaps with or is equal to the third range.

[0057] In order to prevent separation of the particles in the premix, it is important that the particle size distribution of the particles of quicklime and the particle size distribution of the particles of the first additive are close to each other.

[0058] According to a third aspect, the present invention relates to a process for manufacturing a lime-based sorbent suitable for use in a flue gas treatment process, the manufacturing process comprising the following steps:

[0059] - slaking quicklime with water in a hydrator by a non-wet route;

[0060] - Collecting slaked lime at the outlet of the hydrator;

[0061] Characteristically, said process comprises a further step of adding at least a first additive chosen from the group of hydrogel-forming materials of natural or synthetic origin, in particular superabsorbent polymers (SAP) or from the group of cellulose ethers or a combination thereof, said first additive being added before, during or after said slaking step in a weight ratio of between 0.2% and 10%, preferably at most 5%, more preferably at most 2.5%, relative to the weight of said slaked lime, wherein said amount of slaked lime is expressed in equivalent CaO and said first additive in dry equivalent form after drying at 150° C. until constant weight.

[0062] Preferably, in the manufacturing process according to the present invention, the first additive is selected from:

[0063] - the group of hydrogel-forming materials of synthetic origin, which includes cross-linked polyacrylates or cross-linked acrylamide and acrylate copolymers, in particular those partially neutralized with sodium and / or potassium,

[0064] - the group of hydrogel-forming materials of natural origin, which include guar gum, alginate, dextran or xanthan gum or a combination thereof, or

[0065] - The group of cellulose ethers which comprises hydroxyalkyl or carboxyalkyl cellulose ethers, in particular carboxymethyl cellulose or hydroxyethyl methyl cellulose (HEMC).

[0066] In the meaning of the present invention, the term "hydrator" refers to conventional single-stage or multi-stage hydrators or mixers.

[0067] According to the present invention, the term "slaking by a non-wet route" means slaking quicklime by:

[0068] In the manufacturing process according to the invention, the step of slaking is a slaking mode by a "non-wet route", which refers to a slaking mode by a dry route, by a quasi-dry route or by a semi-dry route. In the non-wet route, the amount of water relative to the amount of quicklime is between 0.6 and 1.2. The expression "non-wet route" excludes both slaking modes by a wet route and by a putty route. Each of these slaking routes is defined below.

[0069] In the dry hydration of quicklime, meaning the slaking mode "by dry route", the mass ratio of water to quicklime used to slake the quicklime by dry route is between 0.6 and 0.7.

[0070] In the quasi-dry hydration of quicklime, as another slaking mode, hydration can be achieved with a large excess of water, the mass ratio of water to quicklime for the quasi-dry hydration of quicklime being between 0.85 and 1.2.

[0071] In the semi-dry hydration of quicklime, the mass ratio of water used to slake the quicklime to quicklime is between 0.7 and 0.85.

[0072] In the slaking mode by the wet route, the amount of water added is a very large excess compared to the amount strictly required for the slaking reaction, the mass ratio of water to quicklime used to slake the quicklime being typically greater than 1.5. A milk of lime (i.e. an aqueous suspension of slaked lime particles) is then obtained.

[0073] In the slaking mode "via putty route", the amount of water used for the slaking reaction is slightly lower than that for slaking "via wet route", the mass ratio of water to quicklime used to slake quicklime is typically greater than 1.2 and less than 1.5, and the product obtained is a paste (lime paste).

[0074] In the manufacturing process according to the invention, the first additive is at least partly provided in the form of a solution or suspension and is added to the water and / or the slaked lime, and / or the first additive is at least partly provided in the form of a solid and is added to the quicklime and / or the slaked lime.

[0075] Preferably, the manufacturing process according to the invention comprises a step of mixing powdered slaked lime with said first additive in powder form.

[0076] In an embodiment of the process for manufacturing a lime-based adsorbent according to the present invention, the manufacturing process comprises the following steps:

[0077] - slaking quicklime with water by a non-wet route in a hydrator;

[0078] - Collecting slaked lime at the outlet of the hydrator;

[0079] - optionally, drying the slaked lime;

[0080] - optionally, grinding the slaked lime;

[0081] - Optionally, the slaked lime is subjected to air classification and / or sieving to obtain a slaked lime having a max and d min slaked lime having a particle size distribution within a defined first particle size range;

[0082] - providing the first additive, the first additive having a max and d min The first additive is mixed with a particle size distribution within a second particle size range defined by d, the second particle size range overlapping with the first particle size range or within the first particle size range, and the first additive is mixed with a particle size distribution within a second particle size range defined by d max and d min The slaked lime is mixed with a particle size distribution within a defined first particle size range.

[0083] Preferably, the first additive is provided with a d max and a d of at least 1 μm min and the powdered slaked lime is air classified or sieved to have a particle size distribution between 1 μm and 200 μm, alternatively between 1 μm and 20 μm, alternatively between 5 μm and 20 μm, alternatively between 20 μm and 35 μm, alternatively between 20 μm and 50 μm, alternatively between 50 μm and 100 μm, alternatively between 50 μm and 150 μm, alternatively between 100 μm and 200 μm.

[0084] In one embodiment of the present invention, the manufacturing process includes a preliminary step of particle cutting of slaked lime particles and particle cutting of separating additive particles to remove a portion of particles below a predetermined value and above a predetermined value to provide slaked lime particles and additive particles with similar particle size distributions to prevent separation of slaked lime particles from additive particles. The particle cutting step can be performed by passing the slaked lime and / or additive particles through a series of sieves with predetermined mesh sizes or by passing the slaked lime and / or additive particles through an air classifier.

[0085] In one embodiment, the additives and / or slaked lime are ground prior to or in lieu of these particle cutting steps.

[0086] In another embodiment of the manufacturing process according to the invention, the process comprises the following steps:

[0087] - Provided with max and d min quicklime having a predetermined particle size distribution within a defined third particle size range;

[0088] - Provided with max and d min The first additive has a particle size distribution within a fourth particle size range defined by d, the fourth particle size range overlapping with the third particle size range or within the third particle size range, and the first additive is combined with a max and d min mixing said quicklime having a particle size distribution within a defined third particle size range to form a premix;

[0089] - slaking the premix by a non-wet route in a hydrator to obtain slaked lime comprising the first additive;

[0090] - Collecting slaked lime at the outlet of the hydrator

[0091] - optionally, drying the slaked lime;

[0092] - optionally, grinding the slaked lime;

[0093] - Optionally, sieving or air classifying the slaked lime.

[0094] In an embodiment of the manufacturing process according to the invention, the process further comprises the step of adding, before and / or during and / or after said slaking step, an amount of a second additive, which is a salt or hydroxide of an alkali metal, the amount of which is sufficient to obtain a content of alkali metal in said adsorbent, expressed as an equivalent oxide of said alkali metal, of a weight ratio equal to or greater than 0.2% and equal to or less than 3.5%, based on the total weight of said slaked lime.

[0095] Preferably, the salt or hydroxide of the alkali metal is soluble in water, such as sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium phosphate, sodium persulfate or sodium acetate. Preferably, at 20°C, the alkaline compound has a carbonyl content greater than or equal to 50 g / dm in water. 3 , preferably greater than or equal to 100 g / dm 3 , preferably greater than or equal to 200 g / dm 3 , preferably greater than or equal to 300 g / dm 3 , preferably greater than or equal to 500 g / dm 3 solubility.

[0096] In an embodiment of the manufacturing process according to the invention, the alkali metal salt or hydroxide is provided in solid form or in solution and is added to the water and / or the quicklime and / or the slaked lime. The alkali metal salt or hydroxide may be added before and / or during and / or after the slaking step in the process.

[0097] In an embodiment of the manufacturing process according to the invention, a step of drying the lime-based sorbent and / or a step of particle cutting of the lime-based sorbent and / or a step of grinding or milling the lime-based sorbent is performed.

[0098] Advantageously, in the process according to the invention, the residence time during which the slaked lime is slaked in the hydrator is between 5 and 45 minutes, preferably between 20 and 40 minutes and more preferably between 25 and 35 minutes.

[0099] In another embodiment of the process according to the invention, the quicklime is subjected to particle cutting so as to have particles between a third value range, and the first additive is subjected to particle cutting so as to have particles between a fourth value range, and wherein the third value range overlaps the fourth value range. A step of blending the quicklime with the first additive is then provided before the slaking step.

[0100] According to a fourth aspect, the present invention relates to the use of a lime-based sorbent as disclosed herein and / or obtained from a manufacturing process as presented herein in a flue gas treatment process.

[0101] According to a fifth aspect, the invention relates to a flue gas treatment process in which a gas containing pollutants is circulated through a duct before reaching a particle control device, characterized in that it comprises a step of injection of a lime-based sorbent as presented herein.

[0102] Flue gas treatment can be a cyclic dry scrubber process or a dry sorbent injection (DSI) process.

[0103] The use of the adsorbent according to the invention in a circulating dry scrubber process allows providing a residue capable of carrying more water than prior art residues while maintaining good flowability of the residue in the CDS process, thereby preventing adhesion in tubes, ducts or other parts of a circulating dry scrubber unit or facility.

[0104] The adsorbent according to the present invention provides a residue in a CDS process which exhibits good flowability characteristics even with high moisture content such as greater than 10% by weight in the residue circulating in a circulating dry scrubber unit or plant.

[0105] With a higher water content in the water-carrying sorbent, the performance of the flue gas treatment device is believed to be significantly improved because:

[0106] - Addition of water is believed to help regulate the gas, especially by lowering the reaction temperature and increasing the relative humidity;

[0107] - The added water is believed to help reconstitute the residue so that the remaining Ca(OH)2 can be used again in the reaction;

[0108] - The added water is believed to create locally favorable conditions around the solids in the reactor in order to increase the activity of the sorbent, the reaction products (the added water helps convert the carbonated form of Ca into reactive species with the goal of removing acid gases (SOx, HCl, HF, ...)), and possibly even the fly ash.

[0109] If the same amount of water can be brought into the reactor with a lower amount of recycled material, the size of the conditioning mixer and all related equipment, especially the conveying devices (screws, air slides, ...) is reduced, which can be beneficial for investment costs, and for the facility and maintenance costs of running the CDS process, which will be reduced as less material will be circulated.

[0110] In a flue gas treatment process using a circulating dry scrubber unit or facility, the adsorbent particles will come into contact with the flue gas and form a suspension of reacted adsorbent particles, unreacted adsorbent particles and ultimately other by-products. The suspension is filtered through a particle control device. The flue gas depleted in pollutants is directed to a flue or chimney, and in the CDS unit, the residue formed by the reacted adsorbent particles, unreacted adsorbent particles and ultimately other by-products is redirected and recovered for another cycle. The residue can be recycled and recycled several times. Some fresh adsorbent can also be introduced into the CDS facility at any time. Water is added to reactivate the reacted adsorbent.

[0111] For the adsorbent according to the invention, it is foreseeable to add water to the residue circulating in a circulating dry scrubber (CDS) unit or plant, so as to have a water content of at least 5%, preferably at least 7%, preferably at least 10%, preferably at least 12%, preferably at least 15% by weight relative to the dry mass of the residue.

[0112] Depending on the ratio of sulfur dioxide to HCl in the flue gas treated in the circulating dry scrubber unit or plant, the amount of water added to the residue circulating in the circulating dry scrubber unit or plant can be adjusted.

[0113] For a ratio of sulphur dioxide to HCl greater than 20, the amount of HCl is generally low and it is possible to add water to the residue circulating in the circulating dry scrubber unit or plant so as to have a water content relative to the dry mass which can reach a maximum of 20% by weight without risk of clogging of the residue in the circulating dry scrubber unit or plant.

[0114] For ratios of sulfur dioxide to HCl less than 20, the amount of HCl is generally considered high and may cause more problems with residue plugging in a circulating dry scrubber unit or facility. Therefore, for these ratios of sulfur dioxide to HCl less than 20, the water on the residue circulating in the circulating dry scrubber unit or facility may be such as having a water content of only at least 2% by weight relative to the dry mass of the residue.

[0115] In an embodiment, the flue gas treatment process according to the invention comprises the step of introducing into said circulating dry scrubber unit or facility a sorbent according to the invention or obtained from a manufacturing process as disclosed herein.

[0116] One of the advantages of using a lime-based sorbent according to the present invention in a dry sorbent injection process is that the additive can capture moisture and thereby minimize the sticking of the sorbent in the storage silo or in the injection pipe connected to the flowing gas pipeline.

[0117] Other characteristics and advantages of the invention will emerge from the non-limiting description that follows and by reference to the accompanying drawings and examples.

[0118] Instruction Manual

[0119] Figure 1 A schematic embodiment of a circulating dry scrubber facility for a flue gas treatment process according to the present invention is shown.

[0120] Figure 2 The results of HR-MAS probe analysis of a sodium polyacrylate sample in a semisolid state in a mixture of D2O and CD3CN are shown. 1 HNMR spectrum, the sodium polyacrylate sample was purchased from Aprotek Company as Aproud TM P150XL and this spectrum is similar to that of the adsorbent according to the invention comprising 2.5% by weight of Apromud TM The adsorbent samples of P150XL and the adsorbent samples according to the present invention comprising 10% of Apromud TM The spectra were measured under the same conditions for comparison with the adsorbent samples of P150XL. DETAILED DESCRIPTION

[0121] According to the present invention, a lime-based adsorbent suitable for flue gas treatment process is provided. The lime-based adsorbent comprises:

[0122] - a weight proportion of at least 70% Ca(OH)2, preferably at least 80% Ca(OH)2, more preferably at least 90% Ca(OH)2, more preferably at least 95% Ca(OH)2, relative to the total weight of the lime-based sorbent in dry form after drying at 150°C until constant weight, and;

[0123] - a first additive chosen from hydrogel-forming materials of natural or synthetic origin, in particular superabsorbent polymers (SAP) or from cellulose ethers or combinations thereof, in a weight ratio of at least 0.2% to at most 10%, preferably at least 1% to at most 5%, more preferably at least 1.2% to at most 2.5%, relative to the total weight of the lime-based adsorbent in dry form after drying at 150° C. until constant weight.

[0124] The Ca(OH)2 present in the adsorbent can be measured qualitatively and quantitatively by conventional techniques known to those skilled in the art. The amount of calcium is measured by XRF, the crystal structure of the compound is analyzed by XRD, and the ratio of calcium carbonate and / or calcium oxide (if present) and calcium hydroxide is determined by thermogravimetric analysis on a sample dried at 150°C until constant weight.

[0125] The presence of additives in the adsorbent can be measured qualitatively and quantitatively by NMR. After preparation of a sample which can be dried at 150° C. until constant weight and mixed in a deuterated solvent or a mixture of deuterated solvents (preferably a mixture of D2O and CD3CN), the adsorbent can be measured qualitatively and quantitatively by NMR. 1 HNMR or 13 CNMR or a combination thereof, the additive in the adsorbent is detected using a probe HR-MAS (High Resolution Magic Angle Spinning) for analysis in a semi-liquid state, or by solid state analysis on a solid sample which can be dried at 150°C until constant weight. 1 HNMR or solid state 13 CNMR measures the additive in the adsorbent. Quantitative measurements by NMR can be performed by comparison with a calibration curve obtained by preparing adsorbent samples including various concentrations of the additive. Because the first additive has the property of retaining water, the sample must be dried to constant weight before analysis. Lime-based adsorbents may contain a certain amount of water, for example from the surrounding air or from the manufacturing process.

[0126] The first additive is selected from:

[0127] - the group of hydrogel-forming materials of synthetic origin, which includes polyacrylates, polyacrylic acid, cross-linked polyacrylates and polyacrylic acid or cross-linked acrylamide and acrylate copolymers, in particular those partially neutralized with sodium and / or potassium, or

[0128] - a group of hydrogel-forming materials of natural origin comprising guar gum, alginate, dextran or xanthan gum or a combination thereof, and / or;

[0129] - The group of cellulose ethers which comprises hydroxyalkyl or carboxyalkyl cellulose ethers, in particular carboxymethyl cellulose or hydroxyethyl methyl cellulose (HEMC).

[0130] The highly absorbent polymer is selected from cross-linked polymers of acrylic acid or methacrylic acid, cross-linked graft copolymers of polysaccharide / acrylic acid or methacrylic acid, and cross-linked terpolymers of acrylic acid or methacrylic acid / acrylamide / sulfonated acrylamide and their alkaline earth metal salts or alkali metal salts.

[0131] In an embodiment, the lime-based sorbent according to the present invention further comprises sodium, wherein the amount of sodium in the lime-based sorbent expressed in the form of its equivalent Na2O oxide measured by XRF is at least 0.1%, preferably at least 0.3%, preferably at least 0.5%, preferably at least 0.7%, preferably at most 15%, preferably at most 7%, preferably at most 5%, preferably at most 2.5% sodium by weight relative to the total weight of the sorbent in dry form.

[0132] Preferably, the lime-based adsorbent has a 2 / g, preferably at least 10m 2 / g, more preferably at least 20m 2 / g, preferably at least 40m 2 The BET specific surface area of ​​200 Å / g is measured by nitrogen adsorption manometry after degassing at 190° C. in vacuum for at least 2 hours and calculated according to the multi-point BET method as described in the ISO 9277 / 2010E standard.

[0133] Preferably, the total BJH pore volume of the lime-based adsorbent is at least 0.01 cm 3 / g, preferably at least 0.05cm 3 / g, more preferably at least 0.1cm 3 / g, more preferably at least 0.2cm 3 / g, the total BJH pore volume being determined by nitrogen adsorption manometry after degassing at 190° C. for at least 2 hours in vacuum and calculated according to the multi-point BJH method as described in ISO 9277 / 2010E standard.

[0134] In one embodiment, the lime-based sorbent is a blend of:

[0135] - powdered particles of slaked lime, the powdered particles having a particle size distribution within a first range of values, and;

[0136] - Powdered particles of said first additive having a particle size distribution within a second range of values ​​overlapping or equal to said first range.

[0137] The lime-based adsorbent according to the present invention is obtained by a manufacturing process comprising the following steps:

[0138] - slaking quicklime with water in a hydrator by a non-wet route;

[0139] - Collecting slaked lime at the outlet of the hydrator;

[0140] Characteristically, the process comprises a further step of adding at least a first additive chosen from the group of hydrogel-forming materials of natural or synthetic origin, in particular superabsorbent polymers (SAP) or from the group of cellulose ethers or a combination thereof, before, during or after the slaking step, in a weight ratio of between 0.2% and 10%, preferably at most 5%, more preferably at most 2.5% relative to the weight of the slaked lime, wherein the amount of slaked lime is expressed in equivalent CaO and the amount of the first additive is expressed in dry equivalent form after drying at 150° C. until constant weight.

[0141] Preferably, the first additive is selected from:

[0142] - the group of hydrogel-forming materials of synthetic origin, which includes polyacrylates, polyacrylic acid, cross-linked polyacrylates and polyacrylic acid or cross-linked acrylamide and acrylate copolymers, in particular those partially neutralized with sodium and / or potassium,

[0143] - a group of hydrogel-forming materials of natural origin, which include guar gum, alginate, dextran or xanthan gum or a combination thereof, or

[0144] - The group of cellulose ethers which comprises hydroxyalkyl or carboxyalkyl cellulose ethers, in particular carboxymethyl cellulose or hydroxyethyl methyl cellulose (HEMC).

[0145] In one embodiment of the manufacturing process, the first additive is added before or during the aging step and is at least partially or completely provided in the form of a solution or suspension and added to the water used in the aging step.

[0146] In another embodiment of the manufacturing process, the first additive is added after the slaking step and is provided at least partially or completely in the form of a solution or suspension and is added to the slaked lime, for example by spraying the additive into the collected slaked lime.

[0147] In another embodiment of the manufacturing process, the first additive is added as a powder to the quicklime before the step of slaking.

[0148] In another embodiment of the manufacturing process, said first additive is added to the collected slaked lime after the step of slaking is performed.Preferably, the first additive added after the step of slaking is in the form of a powder.

[0149] In another embodiment of the process for manufacturing a lime-based adsorbent according to the present invention, the process further comprises the step of adding a second additive before and / or during and / or after the slaking step, wherein the second additive is a salt or hydroxide of an alkali metal, and the amount of the salt or hydroxide of the alkali metal is sufficient to obtain a content of alkali metal in the slaked lime expressed as an equivalent oxide of the alkali metal, based on the total weight of the slaked lime, of which the content is equal to or greater than 0.2% and equal to or less than 3.5% by weight.

[0150] Preferably, the alkali metal salt or hydroxide is water-soluble and may be selected from sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium phosphate, sodium persulfate or sodium acetate. Preferably, at 20°C, the alkali metal salt or hydroxide has a carbonyl content greater than or equal to 50 g / dm 3 , preferably greater than or equal to 100 g / dm3 , preferably greater than or equal to 200 g / dm 3 , preferably greater than or equal to 300 g / dm 3 , preferably greater than or equal to 500 g / dm 3 solubility.

[0151] In one embodiment of the manufacturing process, the second additive is added before, during or after the step of ripening and the first additive is added after said step of ripening, preferably in the form of a powder. The second additive may be added in the form of a powder or in the form of a solution.

[0152] In the manufacturing process of the lime-based sorbent according to the present invention, the residence time during which the quicklime is slaked in the hydrator is preferably between 5 and 45 minutes, preferably between 20 and 40 minutes, and more preferably between 25 and 35 minutes.

[0153] In an embodiment of the process for manufacturing a lime-based sorbent, wherein the first additive is added before or during the step of slaking, the process further comprises a step of drying said lime-based sorbent and / or a step of particle cutting of said lime-based sorbent and / or grinding or milling said lime-based sorbent.

[0154] In another embodiment of the process for manufacturing a lime-based sorbent, wherein the first additive is added to slaked lime after the step of slaking, the process further comprises:

[0155] - a step of particle cutting the collected slaked lime to remove some particles outside the first value range, and;

[0156] - a step of subjecting said first additive in powder form to particle cutting so as to remove a portion of the particles outside a second numerical range overlapping with or equal to the first numerical range, so as to provide slaked lime particles and first additive particles having similar particle size distributions, and;

[0157] - Blending the slaked lime and the first additive in a homogenizing device.

[0158] In another embodiment of the manufacturing process according to the present invention, the process comprises the following steps:

[0159] - Provided with max and d min quicklime having a predetermined particle size distribution within a defined third particle size range;

[0160] - Provided with max and d minThe first additive has a particle size distribution within a fourth particle size range defined by d, the fourth particle size range overlapping with the third particle size range or within the third particle size range, and the first additive is combined with a max and d min mixing the quicklime having a particle size distribution within a defined third particle size range to form a premix;

[0161] - slaking said premix by a non-wet route in a hydrator to obtain slaked lime comprising said first additive;

[0162] - collecting slaked lime at the outlet of the hydrator;

[0163] - optionally, drying the slaked lime;

[0164] - optionally, grinding the slaked lime;

[0165] - Optionally, sieving or air classifying the slaked lime.

[0166] For example, the first additive may be classified to have a d greater than or equal to 1 μm. min and d less than or equal to 200 μm max The powdered slaked lime is classified as having a particle size distribution of greater than or equal to 1 μm. min And 200μm d max , and alternatively having a d greater than or equal to 1 μm min and less than 20 μm max , alternatively having a d greater than or equal to 5 μm min and less than 20 μm max , alternatively having a d greater than or equal to 20 μm min and less than 35μm d max , alternatively having a d greater than or equal to 20 μm min and less than 50μm d max , alternatively having a d greater than or equal to 50 μm min and less than 100 μm d max , alternatively having a d greater than or equal to 50 μm min and less than 150μm d max , alternatively having a d greater than or equal to 100 μm min and less than 200 μm d max Particle size distribution.

[0167] In an embodiment of the manufacturing process according to the invention, the first additive is added to quicklime before the step of slaking to form a premix, which is provided to the hydrator for the step of slaking. For a plant having a flue gas treatment plant and a hydrator, providing a premix comprising quicklime and at least the first additive may be advantageous in terms of logistics and costs.

[0168] The premix according to the invention comprises:

[0169] - quicklime in a proportion by weight of at least 70%, more preferably at least 85%, relative to the total weight of said premix in dry form after drying at 150° C. until constant weight, and;

[0170] - a first additive chosen from the group of hydrogel-forming materials of natural or synthetic origin, in particular superabsorbent polymers (SAP), or from the group of cellulose ethers, or a combination thereof, in a weight proportion of at least 0.2% to at most 10%, preferably at least 1% to at most 5%, more preferably at least 1.2% to at most 2.5%, relative to the total weight of said premix in dry form after drying at 150° C. until constant weight.

[0171] Preferably, in the premix, the powdered quicklime and the powdered first additive are in the form of a powder blend comprising:

[0172] - Powdered particles of quicklime, the powdered particles having a max Value and d min a particle size distribution within a third range of values, and;

[0173] - powdery particles of the first additive, the powdery particles having a max Value and d min The particle size distribution is within a fourth range of values, and the fourth range overlaps with or is equal to the third range.

[0174] In the embodiment of the premix, quicklime is provided preferably after the grinding step and optionally after the particle cutting step, the quicklime having a first group d min Value and d max The particle size distribution defined by the second set d min Value and d max Advantageously, the quicklime or one of the first additives has a particle size distribution defined by a value of 50 The value is included in another d min Value and d max Preferably, the d of both the quicklime and the first additive is between 50The values ​​are included in each other's min Value and d max The same particle size distribution of quicklime and the first additive advantageously prevents separation of the two compounds.

[0175] In another embodiment, the premix may further contain the second additive.

[0176] The lime-based sorbent according to the invention obtained from the process described herein is advantageously used in a flue gas treatment process comprising a cyclic dry scrubber process or a dry sorbent injection process.

[0177] The invention also relates to a flue gas treatment process in which pollutant-containing gases are circulated through a duct before reaching a particle control device, characterized in that it comprises a step of injection of a lime-based sorbent as disclosed herein.

[0178] In one embodiment, the flue gas treatment process is a circulating dry scrubber process. Circulating dry scrubber (CDS) units or facilities are well known in the art and are operated to remove pollutants from flue gases. CDS technology was first developed for SO2 removal in coal-fired power plants. Today, it is also used for flue gas treatment of industrial furnaces and boilers that use biomass, industrial or municipal waste as fuel. The CDS process is capable of removing acidic gas components and micropollutants. It is based on the recycling of filter residues including adsorbent reaction products and fly ash from filters. The CDS unit operates using calcium-based adsorbents.

[0179] exist Figure 1 A non-limiting example of a CDS is shown in . The CDS facility 100 is arranged downstream of a gas burner 200, which is connected to the bottom of a reactor 102 by a first pipe 101. A reservoir 107 containing fresh adsorbent is connected to the bottom of the reactor 102 by a second pipe 108, and a metering device 109 is arranged between the second pipe and the bottom of the reactor for injecting fresh adsorbent when needed. The gas 300 containing pollutants flows from the burner 200 through the first pipe 101, then passes through the reactor 102, where the pollutants react with the fresh adsorbent, and then the gas and part of the reacted adsorbent are filtered by a particle filter device 103 arranged downstream of the reactor 102 and upstream of the chimney 110. The particle filter device 103 includes a plurality of bag filters 104. The reacted adsorbent, unreacted adsorbent and optionally fly ash collected in the bag filters 104 form a residue. The collected residue is removed from the bag filter 104 and falls into the hopper 105 at the bottom of the particle filtration device 103, while the flue gas depleted in pollutants is discharged through the chimney 110. The residue is directed to a conditioning mixer 106 comprising a mixer shaft 111 and wherein water is added to reactivate the residue before it is recycled into the reactor 102.

[0180] In a flue gas treatment process using a circulating dry scrubber unit or facility according to the present invention, a fresh lime-based sorbent as disclosed herein is introduced into the CDS facility. The sorbent according to the present invention is able to provide a residue having good flowability in the CDS process, thereby preventing adhesion in tubes, ducts or other parts of the circulating dry scrubber unit or facility. The sorbent according to the present invention is able to release the water of the adhesion agent at low temperatures, typically at the temperatures of the circulating dry scrubber unit or facility between 50°C and 350°C. The lime-based sorbent according to the present invention provides a residue in the CDS process that exhibits good flowability characteristics, even with a high moisture content, also called carryover water, for example a weight ratio of more than 10% in the residue circulating in the circulating dry scrubber unit, relative to the total weight of said sorbent in dry form.

[0181] In one embodiment, the flue gas treatment process is a dry sorbent injection (DSI) process. This process is simpler than the cyclic dry scrubber process and includes the step of dry injecting a lime-based sorbent as described herein into the flue gas before a filtration unit (usually a bag filter) or an electrostatic precipitator. The lime-based sorbent reacts with the pollutants in a single pass.

[0182] The reaction between the gas phase pollutants and the sorbent takes place in the reactor or flue gas duct and continues in the filter, in particular using bag filters. The reaction products and fly ash from the process are captured by downstream filtering equipment.

[0183] One of the advantages of using the lime-based sorbent according to the present invention in a dry sorbent injection process is that the first additive can capture moisture and thereby minimize the sticking of the sorbent in the storage silo or in the injection pipe connected to the flowing gas pipeline.

[0184] Example -

[0185] Description of the pilot plant

[0186] The experiments were carried out in a CDS test unit comprising three main units connected together: a reactor, a filtering means and a mixing zone. The reactor was a Venturi reactor and comprised a vertical thermally insulated pipe (7 m long, 4 cm diameter).

[0187] The bottom of the reactor includes an inlet for injecting a synthesis gas stream containing acid gases (N2, O2, H2O, CO2, SO2). The synthesis gas flows through the reactor and then flows through a fabric bag filter, which is arranged on the top of the reactor and includes 6 sleeves, each sleeve having a 0.1m 2 surface.

[0188] The temperature of the synthesis gas stream was measured at the bag filter and controlled at the bottom of the reactor by heating resistors to 100°C at the bag filter.

[0189] The bottom of the reactor includes an inlet for fresh adsorbent injection and an inlet for recycled material injection, which is reacted fresh adsorbent that has been circulated through the reactor at least once. The fresh adsorbent is introduced into the bottom of the reactor by pneumatic conveying, while the recycled material is introduced into the bottom of the reactor by a metering screw. The injection rate of the fresh adsorbent ranges from 0 to 300 g / h and the injection rate of the recycled material ranges from 0 to 6000 g / h.

[0190] Solid particles of fresh adsorbent and / or recycled material are entrained by the gas stream through the reactor to the fabric filter. The fabric filter (filtering means) separates the gas from the solid particles including at least part of the reacted fresh adsorbent and recycled material (residue).

[0191] The solid residue is then stored and conveyed through three hoppers equipped with butterfly valves: a buffer hopper, an extraction hopper (where a fixed amount of product is taken out to maintain mass balance in the system in case of fresh adsorbent injection) and a weighing hopper. The residue is then metered into the conditioning mixer (mixing zone) via a conveying screw.

[0192] In the conditioning mixer, a given amount of water is thoroughly mixed with the recycled material. The water content added to the recycled material can vary from 0.1% to 30% by weight relative to the total weight of the adsorbent fed into the mixer. The water is injected into the mixer through a stainless steel hollow cone nozzle.

[0193] The regulating mixer includes an elongated receiver including two shafts extending from a first end to a second end. The regulating mixer receiver has a diameter of about 7 dm. 3The capacity of the receiver. A first inlet for introducing the residue into the receiver is arranged near the first end of the receiver, and a water injection nozzle is arranged downstream of the first inlet and in the vicinity of the first inlet for introducing water into the receiver and for humidifying the residue. An outlet for discharging the humidified residue from the receiver is arranged at the bottom of the receiver near the second end of the receiver. Two shafts are arranged parallel to each other in the receiver and are provided with directional flat blades with interpenetrating rotation (center flow direction). The shafts are fitted into a cylinder with a first diameter D1, and the outermost ends of the blades are fitted into a cylinder with a second diameter D2. The central axes of the two shafts are strictly spaced apart from each other at a distance greater than the first diameter D1 and less than the second diameter D2. The bottom of the receiver is shaped as a double circular bottom that matches the rotating cylinder formed by the blades, and so that the blades never touch the double circular bottom of the receiver. Each blade of one of the shafts is offset from the blade of the other shaft to allow the shaft to rotate. Each blade of the same shaft is radially offset at an angle of 120° relative to the adjacent blade. Near the first end of the receiver, both shafts comprise two first blades oriented at 20° relative to the longitudinal axis of the shaft in order to convey the residue under the water injection nozzle. Both shafts further comprise five blades arranged downstream of the two first blades and oriented at an angle of 50° relative to the longitudinal axis of the shaft in order to generate strong back mixing and thus accumulate the residue in the mixing zone. Both shafts further comprise four last blades arranged downstream of the five blades and oriented at an angle of 20° relative to the longitudinal axis of the shaft in order to gradually push the moistened residue out of the mixer. Such regulating mixers are commonly used in CDS facilities.

[0194] After the mixer, the moistened residue falls into a longitudinal hopper equipped with a bridge breaker and a conveying screw to reintroduce the moistened residue in the reactor.

[0195] The performance of the adsorbent according to the invention and of a comparative adsorbent were tested in a CDS test unit.

[0196] A test program was implemented to evaluate the response of converted solid material (less than 10% free lime) circulating in the plant to increasing amounts of water added to the recirculating material in the conditioning mixer, in terms of product adhesion and overall CDS process operability.

[0197] In the first phase of the test protocol, the initially unreacted fresh adsorbent under consideration is placed in the presence of SO2 and CO2 to obtain an adsorbent converted into a residue. The conversion of the adsorbent into the residue is considered to be achieved when the weight ratio of available lime Ca(OH)2 measured in the residue is lower than 10%. In order to accelerate the conversion of the adsorbent, the unreacted fresh adsorbent is added immediately at the beginning of the test and no further fresh adsorbent is added at a later stage.

[0198] In the second phase of the test protocol, the residue was recycled in the CDS test unit while gradually increasing the amount of water added to the conditioning mixer until problems such as pressure drop, plugging, mushy residue appeared in the CDS test unit. The highest amount of water (in % w / w) achieved that still resulted in nominal operation was considered as the result of this test. It is desirable to have a residue that can flow in the CDS test unit at relatively high humidity values. Therefore, the adsorbent provided with such a residue in the CDS test unit is more efficient in SO2 absorption and can be regenerated more times and recycled for longer periods of time, resulting in reduced consumption of the adsorbent.

[0199] Comparison example -

[0200] In the comparative example, the fresh adsorbent used is a slaked lime sample that does not include any additives. This slaked lime is industrially produced in one of the applicant's hydration plants. In this plant, 4t / h is used to supply 0-3mm quicklime and water to a three-stage hydrator (Pfeiffer). The amount of water is adjusted so that the moisture content in the product coming out of the hydrator is less than 1% as a target. The moisture content is measured by the loss when drying at 150°C. The temperature in the hydrator is also used as a process control parameter, especially the temperature measured in the second stage, which should typically vary between 100°C and 105°C. From the outlet of the hydrator, the product is brought to an air classifier by a conveying screw and a bucket elevator. In this classifier, the product is cut into a coarse part (typically >65μm) and a fine part (typically <65μm), and the latter is then directly sent to a storage bin. The slaked lime of the comparative example presents the following physical properties:

[0201] - a moisture content of 1% by weight, measured by loss on drying at 150°C,

[0202] -14m 2 Specific surface area BET of 1.3 % by weight, measured by nitrogen adsorption manometry after degassing at 190° C. in vacuum for at least 2 hours and calculated according to the multipoint BET method as described in ISO 9277 / 2010E standard,

[0203] -0.063cm 3 / g of pore volume, determined by nitrogen adsorption manometry after degassing at 190° C. in vacuum for at least 2 hours and calculated according to the BJH method as described in ISO 9277 / 2010E standard, and

[0204] - d98 less than 70 μm, measured by laser granulometry in methanol after sonication at 100 W for 2 minutes.

[0205] The comparative example of slaked lime was tested in the CDS test unit according to the test protocol described above. In the first stage of the test protocol, the CDS test unit was loaded with 4.2 kg of fresh adsorbent. The fresh adsorbent was injected directly into the bottom of the reactor through the reinjection screw. The flow rate of the synthesis gas was set to 25 Nm 3 / h, and its composition is the gas mixture described in Table 1.

[0206] Table 1:

[0207]

[0208] The residue is separated from the gas by a bag filter, which is automatically cleaned with air pulses when the pressure difference on the filter reaches 6 mbar. The residue is then collected and dropped through a hopper in series to a regulating mixer, where the residue is added at a flow rate of 2500 g / h to mix with 250 mL / h of water to obtain 10% moisture retention. The humidified residue is then reintroduced into the bottom of the reactor and recirculated. When the residue shows good performance in terms of flow, for example, when 200 g of the residue can be metered into the reactor in less than 120 seconds, the recirculation flow is usually set to 4000 g / h after 7 hours to mix with 400 mL / h of water to maintain 10% moisture retention.

[0209] Twice a day, separated by a period of at least 3 hours, a first sample of the residue is collected after the mixing zone and a second sample of the residue is collected in a weigh hopper (also equivalent to the reactor outlet) for analysis of the content of carbonates, sulfur species (sulfate or sulfite) and unreacted Ca(OH)2 (available lime). The conversion of the adsorbent into the residue is considered to be achieved when the weight proportion of available lime Ca(OH)2 measured in the residue is lower than 10%.

[0210] In the second phase of the program, the gas flow rate was maintained at 25m 3 / h and the injection of SO2 and CO2 was stopped. The recirculation flow rate of the residue was maintained at 4 kg / h and the humidity in the mixer was increased from 12% in steps of 2% over a period of at least 3 hours until clogging or pressure drop problems occurred.

[0211] For each step of increasing humidity, at least one sample was collected at the filter and outside the mixer for measuring the moisture content of each residue by loss on drying at 150°C.

[0212] For the samples of this comparative example, the highest amount of water added to the mixer that the equipment could properly handle was 18%. Beyond this limit, the facility suffered from many process problems (severe plugging, high pressure drop) caused by the high adhesion of the residue.

[0213] Example 1 -

[0214] In this example, slaked lime of the comparative example has been used as a raw material and blended with a super absorbent polymer having a particle size distribution d of less than 400 μm. max Reticulated sodium polyacrylate, supplied by the company Aprotek (see, for example, FR 3029195) and marketed under the name Apromoud TM P150XL commercialization. The superabsorbent polymer was used as received and already contained 5% of moisture (measured by loss on drying at 150°C), which may have come from air trapped during handling and storage (storage at temperatures between 0°C and 35°C). To produce 5 kg of the blend, 487.5 g of slaked lime described above and 12.5 g of Apromud TM P150XL 10 batches in The 10 batches were then put together in a 20 L capacity planetary mixer (Hobart brand) where they were mixed to produce a single batch of 5 kg. This batch contained 2.5% by weight of Apromud TM P150XL. Prepare another sample in the same manner, adjusting the amount to obtain a 10% Apromud TM Batch of P150XL.

[0215] Prior to testing in the CDS test unit, the analysis contained 2.5% of Apromud TM The blend of P150XL and its main characteristics are shown below:

[0216] – a moisture content of 1.1% by weight, measured by loss on drying at 150°C,

[0217] -14.2m 2 Specific surface area BET of 1.3 % by weight, measured by nitrogen adsorption manometry after degassing at 190° C. in vacuum for at least 2 hours and calculated according to the multipoint BET method as described in ISO 9277 / 2010E standard,

[0218] -0.065cm 3 / g of pore volume, determined by nitrogen adsorption manometry after degassing at 190° C. in vacuum for at least 2 hours and calculated according to the BJH method as described in ISO 9277 / 2010E standard, and

[0219] - d98 less than 80 μm, measured by laser granulometry in methanol after sonication at 100 W for 2 minutes.

[0220] Further through 1 HNMR Characterization of 2.5% and 10% Apromud TM P150XL blend.

[0221] The additive was partially dissolved in a mixture of water and acetonitrile to prepare the problem solution. 15 mg of powdered Apromud TM P150XL was mixed with 15 μl of D2O and 35 μl of CD3CN in a vial and stirred vigorously for a few seconds to obtain a problem solution, 1 The solution in question was analyzed by HNMR using a probe HR-MAS (High Resolution Magic Angle Spinning) specifically designed for semi-solid mixtures. 64 scans were recorded at ambient temperature. 1 HNMR spectroscopy, the 1 The HNMR spectrum has a water peak presaturation and a 5000 Hz rotation. TM The gelation performance of P150XL in the presence of water, most of the signals are large. Apromud TM The spectrum of P150XL is Figure 2 It is shown with reference numeral 1 in the figure.

[0222] 15 μg of 10% Apromud TM The powdered blend of P150XL was mixed with 20 μl of CD3CN and 40 μl of D2O in a vial to form a slurry. 1 The slurry was analyzed by HNMR using a probe HR-MAS (High Resolution Magic Angle Spinning) specifically for semi-solid mixtures. 64 scans were recorded at ambient temperature. 1 HNMR spectroscopy, the 1 The HNMR spectrum has a water peak presaturation and a rotation of 5000 Hz. Contains 10% Apromud TM The spectrum of the blends of P150XL is Figure 2 It is shown with reference numeral 2 in the figure.

[0223] Add 15 μl of 2.5% ApromudTM The powdered blend of P150XL was mixed with 20 μl of CD3CN and 40 μl of D2O to form a slurry. 1 The slurry was analyzed by HNMR using a probe HR-MAS (High Resolution Magic Angle Spinning) specifically for semi-solid mixtures. 64 scans were recorded at ambient temperature. 1 HNMR spectrum, the 1 The HNMR spectrum was presaturated with water and 5000 Hz spinning. 2.5% Apromud TM The spectrum of the blends of P150XL is Figure 2 It is shown with reference numeral 3 in the figure.

[0224] The spectra of the two blends are similar, with the 10% Apromud TM The blends with P150XL have a stronger signal and are comparable to Apromud alone. TM P150XL also has an auxiliary signal of approximately 5 ppm for the most concentrated samples. These blend spectra are similar to those of Apromud alone. TM Comparison with P150XL shows the presence of similar signals, which are Figure 2 surrounded by even in a separate Apromud TM There are some chemical shifts and some additional larger signals in the spectrum of P150XL. TM The different performance of P150XL in water and in the presence of lime may explain the offset and additional signal, where Apromud TM P150XL can completely gel by absorbing water, obtaining a milky solution. Therefore, for relatively low apromud concentrations such as 2.5% by weight of the adsorbent TM P150XL additive can be used using the HR-MAS probe 1 HNMR detection of Apromud in the adsorbent sample according to the present invention TM Concentration of P150XL additive.

[0225] The blend of slaked lime-sodium polyacrylate obtained as above was tested in a CDS test unit according to the test protocol described above. In the first stage of the test protocol, a 4.2 kg amount of fresh adsorbent (i.e., blend of slaked lime-sodium polyacrylate) was loaded in the CDS test unit. The fresh adsorbent was injected directly into the bottom of the reactor by a re-injection screw. The synthesis gas flow rate set in the process was 25 Nm 3 / h, and its composition is the same as that presented in the comparative example in Table 1.

[0226] The residue is separated in a bag filter, which is automatically cleaned with air pulses when the pressure difference on the filter reaches 6 mbar. The residue is then collected and dropped through a hopper in series to a regulating mixer, where the residue is introduced at a flow rate of 2500 g / h to mix with 250 mL / h of water to obtain 10% moisture retention. The humidified residue is then reintroduced into the bottom of the reactor and recirculated. When the residue shows good performance in terms of flow, for example, when 200 g of the residue can be metered into the reactor in less than 120 seconds, the recirculation flow is usually set to 4000 g / h after 7 hours to mix with 400 mL / h of water to maintain 10% moisture retention.

[0227] Twice a day, separated by a period of at least 3 hours, a first sample of the residue is collected after the mixing zone and a second sample of the residue is collected in a weigh hopper (also equivalent to the reactor outlet) for analysis of the content of carbonates, sulfur species (sulfate or sulfite) and unreacted Ca(OH)2 (available lime). The conversion of the adsorbent into the residue is considered to be achieved when the weight proportion of available lime Ca(OH)2 measured in the residue is lower than 10%.

[0228] In the second phase of the program, the gas flow rate was maintained at 25m 3 / h and the injection of SO2 and CO2 was stopped. The recirculation flow rate of the residue was maintained at 4 kg / h and the humidity in the mixer was increased from 12% in steps of 2% over a period of at least 3 hours until clogging or pressure drop problems occurred.

[0229] For each step of increasing humidity, at least one sample was collected at the filter and outside the mixer for measuring the moisture content of each residue by loss on drying at 150°C.

[0230] For the sample illustrated, the highest amount of water added to the mixer that the equipment could properly handle was 28%. Beyond this limit, the residue became too viscous and the process no longer worked.

[0231] Therefore, the blend slaked lime-sodium polyacrylate according to the invention was able to run longer in a CDS test unit with a higher moisture content than slaked lime with similar physical properties but without additives.

Claims

1. A flue gas treatment process in which a gas containing pollutants is circulated through a duct before reaching a particle control device, characterized in that The flue gas treatment process includes an injection step of a lime-based sorbent; the flue gas treatment process includes a circulating dry scrubber process; the lime-based sorbent is maintained in a multiple pass cycle through a CDS facility in the flue gas treatment; the lime-based sorbent includes: - at least 70% by weight of Ca(OH)2 relative to the total weight of said lime-based sorbent in dry form after drying at 150°C until constant weight, and; - a first additive in a proportion by weight of at least 0.2% and at most 10% relative to the total weight of said lime-based adsorbent in dry form after drying at 150° C. until constant weight, said first additive being chosen from the group of hydrogel-forming materials of natural or synthetic origin and from the group of cellulose ethers, The group of hydrogel-forming materials of synthetic origin includes polyacrylates, polyacrylic acid, cross-linked polyacrylates and polyacrylic acid, or cross-linked acrylamide and acrylate copolymers, The group of hydrogel-forming materials of natural origin includes guar gum, alginate, dextran or xanthan gum or a combination thereof; The lime-based adsorbent has a BET specific surface area of ​​at least 3 m² / g, the BET specific surface area being measured by nitrogen adsorption manometry after degassing at 190° C. in vacuum for at least 2 hours and calculated according to the multi-point BET method described in ISO 9277 / 2010E standard, and the lime-based adsorbent has a total BJH pore volume of at least 0.01 cm³ / g, the total BJH pore volume being determined by nitrogen adsorption manometry after degassing at 190° C. in vacuum for at least 2 hours and calculated according to the multi-point BJH method described in ISO 9277 / 2010E standard.

2. The flue gas treatment process according to claim 1, wherein the first additive is selected from a highly absorbent polymer; or The group of cellulose ethers includes hydroxyalkyl or carboxyalkyl cellulose ethers.

3. The flue gas treatment process according to claim 2, wherein the highly absorbent polymer is selected from a cross-linked polymer of acrylic acid or methacrylic acid, a cross-linked graft copolymer of polysaccharide / acrylic acid or methacrylic acid, and a cross-linked terpolymer of acrylic acid or methacrylic acid / acrylamide / sulfonated acrylamide and its alkaline earth metal salt or alkali metal salt.

4. The flue gas treatment process according to any one of claims 1 to 3, wherein the lime-based sorbent further comprises sodium, wherein the amount of sodium in the lime-based sorbent expressed in the form of its equivalent Na2O oxide measured by XRF is at least 0.1% by weight relative to the total weight of the sorbent in dry form.

Citation Information

Patent Citations

  • Process for manufacturing a sorbent for a flue gas treatment process, sorbent and use of said sorbent in such flue gas treatment process

    WO2018185328A1

  • Nouvelle composition pour faciliter le transport des boues

    FR3029195A1

  • Process for flue gas treatment and products for use in said process

    WO2018184702A1